NEUROD1 Is Required for the Early α and β Endocrine Differentiation in the Pancreas - Bohuslavova, Romana; Smolik, Ondrej; Malfatti, Jessica; Berkova, Zuzana; Novakova, Zaneta; Saudek, Frantisek; Pavlinkova, Gabriela (International journal of molecular sciences, 2021)
Diabetes is a metabolic disease that involves the death or dysfunction of the insulin-secreting β cells in the pancreas. Consequently, most diabetes research is aimed at understanding the molecular and cellular bases of pancreatic development, islet formation, β-cell survival, and insulin secretion. Complex interactions of signaling pathways and transcription factor networks regulate the specification, growth, and differentiation of cell types in the developing pancreas. Many of the same regulators continue to modulate gene expression and cell fate of the adult pancreas. The transcription factor NEUROD1 is essential for the maturation of β cells and the expansion of the pancreatic islet cell mass. Mutations of the Neurod1 gene cause diabetes in humans and mice. However, the different aspects of the requirement of NEUROD1 for pancreas development are not fully understood. In this study, we investigated the role of NEUROD1 during the primary and secondary transitions of mouse pancreas development. We determined that the elimination of Neurod1 impairs the expression of key transcription factors for α- and β-cell differentiation, β-cell proliferation, insulin production, and islets of Langerhans formation. These findings demonstrate that the Neurod1 deletion altered the properties of α and β endocrine cells, resulting in severe neonatal diabetes, and thus, NEUROD1 is required for proper activation of the transcriptional network and differentiation of functional α and β cells.
Keywords: buněčná diferenciace; pankreas; Animals, Newborn; Pancreas; Cell Proliferation; Mice, Inbred C57BL; Animals; Diabetes Mellitus; Islets of Langerhans; mouse model; Mice, Transgenic; Mice; transkripční faktory bHLH; myši inbrední C57BL; Gene Expression Regulation, Developmental; pancreatic development; buněčný rodokmen; Cell Lineage; Female; novorozená zvířata; NEUROD1; vývojová regulace genové exprese; inzulin; proliferace buněk; genetic mutation; transcriptional network; ženské pohlaví; diabetes mellitus; Cell Differentiation; Insulin; myši transgenní; zvířata; Basic Helix-Loop-Helix Transcription Factors; Langerhansovy ostrůvky; beta-buňky; myši; Insulin-Secreting Cells